Hubungan Pengetahuan Terhadap Pola Penggunaan Kombinasi Obat Natrium Diklofenak dan Dexamethasone di Mayarakat Desa Sidomulyo - Rahmaniah Dewi; Ekanita Desiani (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Sodium diclofenac and dexamethasone are anti-inflammatory drugs that are often combined with a doctor's prescription or without a doctor's prescription. The people of Sidomulyo Village often consume these combination drugs. However, the public does not yet know that long-term use has dangerous side effects. The people of Sidomulyo have low education, which affects knowledge in using drug combinations. The latest in this research lies in the research instrument, namely the research questionnaire. The purpose of this study is to determine the relationship between knowledge and patterns of use of the combination of sodium diclofenac and dexamethasone drugs. This type of research is non-experimental using a descriptive design with a quantitative approach. The research sample with this inclusion criterion is people who use a combination of these drugs with a total of 98 respondents. The instrument used, namely a questionnaire, was compiled by the researcher and a validity and reliability test has been carried out with the results of the average validity test value of 0.361 and the reliability test value of 0.863, so it is declared valid and reliable. The characteristic results with the inclusion criteria of most people using this combination of drugs at the age of 45-59 years were (52%) of 51 respondents, female was (68%) of 67 respondents. The results of bivariate analysis using the Chi Square test obtained a p value of 0.05. Thus, it can be concluded that there is a relationship between the level of knowledge and the pattern of use of the combination of sodium diclofenac and dexamethasone.